Optimalisasi Peran Kader dalam Edukasi Hidup Sehat dan Gizi Seimbang untuk Mencegah Kanker - Eka Rudy Purwana; Chandra Irawan; Akhmad Fathoni; Hardiansyah (Fakultas Ilmu Pendidikan dan Psikologi, 2025)
The 2025 Community Service Program (KKN) of the Mataram Ministry of Health Polytechnic was held in Rempung Timur Utara Hamlet, Rempung Village, Pringgasela District, East Lombok Regency. The background to this activity was the high prevalence of stunting, low immunization coverage, and the increasing number of Non-Communicable Diseases (NCDs), especially cancer, which pose a serious threat to public health. The overall objective of this activity was to implement Interprofessional Collaborative (IPC) through the flagship SIGAP program (Prepare a Generation Against Stunting, Complete Immunization, and Cancer Awareness). Specifically, students were targeted to be able to identify health problems, conduct screenings and examinations, educate, and empower communities of all ages, from infants to the elderly. The theory used was based on the IPC-based public health approach, which prioritizes collaboration across professions (nursing, midwifery, nutrition, and medical laboratory technology). This approach aligns with the Ministry of Health's promotive-preventive paradigm. The research method used was a participatory approach using the Participatory Action Research (PAR) model, in which students, along with the community, village officials, religious leaders, and health workers, actively participated in planning, implementation, and evaluation. Data were obtained through field observations, discussions, health checks, demonstrations, and outreach. The research implementation process began with the preparation of a proposal and Plan of Action (POA), followed by the acceptance of KKN students, village community meetings (MMD), and implementation of activities. Interventions included education on balanced nutrition and stunting, demonstrations of local food processing (NATELOR) (chicken nuggets, tempeh, eggs, and moringa), hemoglobin level checks for pregnant women, immunization counseling, education on cervical and breast cancer, demonstrations of Breast Self-Examination (BSE), blood pressure checks, a health expo (Rempung Besopoq), and demonstrations of Handwashing with Soap (CTPS) in elementary schools. The results showed an increase in community knowledge about nutrition, immunization, cancer, and hygienic living practices. Hb checks for pregnant women identified cases of anemia, which increases the risk of stunting, while blood pressure checks detected several cases of hypertension in adults and the elderly. The NATELOR program was praised as an innovation in nutritious local food, while the CTPS (Hand-Hearted Handwashing) activity successfully reached 70 elementary school students. The discussion emphasized that issues of nutrition, immunization, and NCDs must be addressed comprehensively through cross-professional synergy. Community-based promotive and preventive efforts have proven effective in increasing community awareness and involvement. However, obstacles such as time constraints and limited target coverage were still encountered. This activity concluded that the implementation of IPC in KKN (Community Service Program) successfully increased community knowledge, awareness, and participation in stunting prevention, immunization strengthening, and early cancer detection. This activity not only impacted the community but also provided students with practical experience in cross-professional collaboration.